Elaboración de una guía descriptiva de flora y fauna de la comunidad de Paquiestancia de la parroquia Ayora del cantón Cayambe en la provincia de Pichincha. - Paredes Chasipanta, Bryan Mauricio (2021)
The biodiversity floristic and faunistic in Ecuador is very significantly, considered the one country in America Latina small with very biodiversity worldwide in the year 2020 it was one of the five most biodiverse country in the world in a publication of the national geographic, In this context is necessary to know about natural resources that country has. For this reason, we made an inventory in the Community Paquiestancia. This community is located in Parroquia Ayora Canton Cayambe; here, we can still find the remnant tall montane evergreen forest of the Western Cordillera of the Andes. The forest is incredibly dynamic, with extraordinary endemism of fauna and diverse environments of the forest. It is also the home of different species animals, being regulators water, within the aspect investigative, were objectives proposed which allowed the realization of the flora and fauna guide descriptive. The use of the qualitative methodology helped the investigative process and could answer scientific questions raised. The analysis site with the investigation on the investigation in sources secondary and primary allowed the realization of the quick ecological evaluation in the study site, three zones for monitoring of flora and fauna were identified. Here different techniques were applied for faunistic monitoring. Where were established techniques appropriate for each type of vertebrate animals such as direct observation, interviews, camera traps, intensive search, the capture of individuals, linear transects, point counts, tours, species lists, intensive search, and taxonomic cards. Each one of these techniques was used for each type of vertebrate animals such as birds, mammals, amphibians, reptiles, and fish; these monitors were developed during 15 days, in which it was possible to establish a database that collected a total of 50 species of vascular plants and 23 faunal species ( birds:21; mammals:1; fish:1 ). Subsequently, the faunal species were identified and taxonomically classified with a brief description of each animal and plant species. It was also possible to know their current state of conservation with data obtained from the International Union for the Conservation of Nature, it is important to highlight the commitment that exists in this place for the promotion of tourism in this area, thanks to that it was possible to develop this research project without any setback. However, as in every family, there are always aspects to improve. It is the abandonment of the authorities with this community for the development of technical talks to develop tourism technically and responsibly with the environment that also benefits the community.